Re-Stor(y)ing Theatre History in the Americas: Professional Players and the Callao Contract of 1599 - Finque, Susan Beth (My University, 2017)
University of Washington Abstract Re-stor(y)ing Theatre History in the Americas: Professional Players and the Callao Contract of 1599 Susan Finque Chair of the Supervising Committee: Dr. Scott Magelssen In neglecting Peruvian theatre history, theatre studies has kept a branch of American theatre’s genealogical tree nearly invisible, despite the fruits of its growth thriving in plain sight. In investigating a contract drawn in Callao, Peru, 1599, I reveal a culture of secular, professional performance in sixteenth-century Lima. Inarguably creating the first professional company in the Western Hemisphere, the contract features male and female signatories, democratic structure, business sophistication, and a synchronicity with the evolution of the profession in Shakespeare’s London. Players were onstage in the Americas more than a hundred years earlier than current narratives dictate. The contract’s neglect, and English language scholars’ neglect of the Peruvian archives reveal pervasive biases in historiography. Asking how an abundance of archival evidence and the repertory of Peru persist without influencing theatre history in the Americas, I investigate genetic elements in the americanity of Peru, a term defining influences from indigenous, invasive and mestizaje cultures. I theorize with scholars Michel de Certeau, Carolyn Dean, Diana Taylor, Odai Johnson and Joseph Roach, among others, how slow-to-change narratives of theatre history in the Americas lack a hemispheric consciousness and are ruled by a series of persistent hegemonic assumptions. I examine dominant textbooks in order to establish Peru’s absence. Peruvians Inca Garcilaso de la Vega, Guillermo Lohmann Villena and Maria Rostrowowski help track cultural formations in Peru before and after Contact. Examining the contract’s moment in history with a feminist lens enables new perspectives on actors coming to the Spanish Americas. This project registers cultural influences from an understudied Peru, contributions of under-recognized scholars of colonial and pre-Contract Peru, and the collections of Abraham Simon Rosenbach, the Jewish American bookseller who purchased the contract and in 1939 published a paper on his finding. The legacy of Peru’s theatre history reveals the implications and rewards of a hemispheric consciousness for the Americas, and the critical role performance can play in cultures surviving traumatic violence.
Thesis (Ph.D.)--University of Washington, 2017-06
Keywords: Callao; Peru; Sixteenth Century; Susan Finque; Theatre; Yuyachkani; Theater history; Latin American studies; Performing arts; Drama